Epigenetics insights into chronic pain: DNA hypomethylation in fibromyalgia—a controlled pilot-study. Issue 8 (August 2017) - Ciampi de Andrade, Daniel; Maschietto, Mariana; Galhardoni, Ricardo; Gouveia, Gisele; Chile, Thais; Victorino Krepischi, Ana C.; Dale, Camila S.; Brunoni, André R.; Parravano, Daniella C.; Cueva Moscoso, Ana S.; Raicher, Irina; Kaziyama, Helena H. S.; et al.
Abstract : Abstract: To evaluate changes in DNA methylation profiles in patients with fibromyalgia (FM) compared to matched healthy controls (HCs). All individuals underwent full clinical and neurophysiological assessment by cortical excitability (CE) parameters measured by transcranial magnetic stimulation. DNA from the peripheral blood of patients with FM (n = 24) and HC (n = 24) were assessed using the Illumina-HumanMethylation450 BeadChips. We identified 1610 differentially methylated positions (DMPs) in patients with FM displaying a nonrandom distribution in regions of the genome. Sixty-nine percent of DMP in FM were hypomethylated compared to HC. Differentially methylated positions were enriched in 5 genomic regions (1p34; 6p21; 10q26; 17q25; 19q13). The functional characterization of 960 genes related to DMPs revealed an enrichment for MAPK signaling pathway (n = 18 genes), regulation of actin cytoskeleton (n = 15 genes), and focal adhesion (n = 13 genes). A gene–gene interaction network enrichment analysis revealed the participation of DNA repair pathways, mitochondria-related processes, and synaptic signaling. Even though DNA was extracted from peripheral blood, this set of genes was enriched for disorders such as schizophrenia, mood disorders, bulimia, hyperphagia, and obesity. Remarkably, the hierarchical clusterization based on the methylation levels of the 1610 DMPs showed an association with neurophysiological measurements of CE in FM and HC. Fibromyalgia has a hypomethylation DNA pattern, which is enriched in genes implicated in stress response and DNA repair/free radical clearance. These changes occurred parallel to changes in CE parameters. New epigenetic insights into the pathophysiology of FM may provide the basis for the development of biomarkers of this disorder. Abstract : Supplemental Digital Content is Available in the Text.Fibromyalgia has a hypomethylation DNA pattern, which is enriched in genes implicated in stress response and DNA repair, and free radical clearance.